Pengaruh Dana Pihak Ketiga, Loan To Deposit Ratio, Dan Non Perfoming Loan Terhadap Kinerja Keuangan Pada Bank Digital Indonesia - Tri Yunita Sari, Ni Komang; Muliati, Ni Ketut; Pramuki, Ni Made Wisni Arie (UNHI Press, 2025)
The financial performance of a bank reflects the extent to which the bank has succeeded in its operations. Banking financial performance is a crucial element in evaluating the overall achievements of a bank. This includes assessments of assets, liabilities, liquidity, and other elements. A company with optimal financial performance will achieve maximum profits, which in turn will demonstrate a high return on investment. This research investigates the effects of third-party funds, LDR, and NPL on the financial outcomes of digital banks in Indonesia. The study covers all digital banks operating in Indonesia between 2021 and 2023, with a total of 15 banks considered. The sampling process was conducted using a purposive sampling technique, focusing on two main criteria: (1) digital banks located in Indonesia and (2) those that published financial statements for the years 2021-2023. The analysis utilized multiple regression methods to examine the data. The results indicate that third-party funds do not significantly affect the financial performance of digital banks in Indonesia. In contrast, the loan-to-deposit ratio has a substantial and positive impact on financial performance, while non-performing loans do not significantly influence these banks' financial outcomes